Integrating Gender Sensitization and Gender-Neutral Language of English by Employing CLIL Approach to Enhance Critical Thinking - Ravi Prakash Jalli; Spoorthi Boda (Ilha do Desterro)
This study aims to examine how CLIL approach can be employed for integrating gender sensitization and gender-neutral language of English to enhance critical thinking. CLIL stands for Content and Language Integrated Learning approach which integrates content and language, placing equal focus on both. The study uses a cross-sectional pre-experimental research design, following one group: pre-test, intervention and post-test model. Convenience sampling is employed to select the participants: 105 engineering second-year students attending Gender Sensitization MNC at an NIT. The results of the study were analysed using both inductive and descriptive analyses along with inferential statistics. They conclude that CLIL is an effective approach to integrating gender sensitization and gender-neutral language of English to enhance critical thinking.